1985
DOI: 10.1042/bj2310623
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that phorbol ester interferes with stimulated Ca2+ redistribution by activating Ca2+ efflux in neutrophil leucocytes

Abstract: The free calcium ion concentration, [Ca2+]i, in the cytoplasmic matrix of quin2-loaded neutrophil leucocytes increases rapidly after addition of concanavalin A. This increase is effectively abolished by a short (3 min) preincubation with 10 nM-TPA (12-O-tetradecanoylphorbol 13-acetate). TPA also inhibits a [Ca2+]i rise of similar magnitude induced by low concentrations (10 nM) of calcium ionophore A23187, suggesting that phorbol ester does not interfere with a physiological influx mechanism. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Several authors have shown that stimulation of neutrophils by phorbol esters or OAG causes inhibition of agonist-induced and A23187-induced increases in cytosolic Ca2" and speeds the rate of its return towards or below the prestimulation values (e.g. Sha'afi et al, 1983;Fujita et al, 1984;Schell-Frederick, 1984;Rickard & Sheterline, 1985;Naccache et al, 1985;Della Bianca et al, 1986), and we found this too (see Results).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Several authors have shown that stimulation of neutrophils by phorbol esters or OAG causes inhibition of agonist-induced and A23187-induced increases in cytosolic Ca2" and speeds the rate of its return towards or below the prestimulation values (e.g. Sha'afi et al, 1983;Fujita et al, 1984;Schell-Frederick, 1984;Rickard & Sheterline, 1985;Naccache et al, 1985;Della Bianca et al, 1986), and we found this too (see Results).…”
Section: Discussionsupporting
confidence: 65%
“…At least two mechanisms for this effect on calcium are possible: activation of a calcium extruding plasma membrane pump (Lagast et al, 1984;Rickard & Sheterline, 1985), or inhibition of phospholipase Cdependent phosphoinositide turnover in the PMN (Della Bianca et al, 1986), leading to decreased mobilization of cytoplasmic free calcium by inositol trisphosphate. This latter substance is thought to be responsible, at least in part, for calcium mobilization from the endoplasmic reticulum in many cells including neutrophils (Burgess et al, 1984;Prentki et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In PC-12 cells a short term (around 4-10 min) incubation in the presence of TPA leads to a reduction in the rise in cytosolic Ca2+ induced by saturating concentrations of carbachol (Vicentini et al, 1985). Similar short-term effects of TPA on stimulus-induced Ca2 + mobilization have also been observed in other cells where the effects appear, at least in some cases, to be due to an activation of a Ca2+ extrusion mechanism in the cells induced by the phorbol ester through protein kinase C (Rickard and Sheterline, 1985;Tsien et al, 1982b). A more effective Ca2' extrusion mechanism would cause a relative decrease in intracellular Ca2+ stores and thereby limit the rise in cytosolic Ca2+.…”
Section: Discussionmentioning
confidence: 68%
“…However, since TPA has been shown to decrease A23187-or concanavalin Ainduced Ca2+ influx in pig neutrophils (Rickard & Sheterline, 1985), the combined effect by thapsigargin and TPA on arachidonic acid release cannot be explained solely by stimulation of Ca2 + influx. Fourthly, an inhibitor of protein kinases H-7 failed to suppress thapsigargin-stimulated release of radioactivity ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%